PENGEMBANGAN MEDIA GAMIFIKASI MATCHING CARD BERBASIS INTERACTY DAN LEARNINGAPPS UNTUK MENINGKATKAN KOSAKATA ANAK TUNAGRAHITA DI SLB BAITURAHMAN BIMA - Faiz, Muhammad; Fitriati, Ita; Ahyar; Hardiansyah; Irawati, Ika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low vocabulary mastery of animal and plant recognition among students with intellectual disabilities at SLB Baiturahman Bima due to the limited use of interactive learning media. The purpose of this study was to develop a gamified matching card learning media based on LearningApps and Interacty that is feasible and effective in improving vocabulary mastery among students with intellectual disabilities. This study employed the Research and Development (R&D) method using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects were four students with intellectual disabilities at SLB Baiturahman Bima. The feasibility of the media was assessed by two media experts and two material experts, while its effectiveness was measured through pretests and posttests analyzed using the N-Gain formula. The results showed that the developed media achieved an average validation score of 85% from media experts and 89% from material experts, both categorized as highly feasible. The implementation results indicated an improvement in students’ average scores from 55 in the pretest to 87.5 in the posttest. The N-Gain analysis produced a score of 0.7125 or 71.25%, which falls into the high category and indicates that the media is sufficiently effective. These findings demonstrate that the LearningApps and Interacty-based gamified matching card media can effectively improve the vocabulary mastery of animal and plant recognition among students with intellectual disabilities. Therefore, the developed media can serve as an engaging, interactive, and appropriate learning alternative that accommodates the learning characteristics of students with intellectual disabilities.